112k views
0 votes
What is the inverse opperation of f (x)= x+2/3x-4

1 Answer

2 votes

Answer:

Given the function:
f(x) = (x+2)/(3x-4)

Step 1: Replace f(x) by y;


y= (x+2)/(3x-4)

Step 2: Interchange the variables x and y.


x= (y+2)/(3y-4)

Step 3: Solve for y in terms of x;


x(3y-4) = y+2

Using distributive property:
a\cdot (b+c) = a\cdot b+ a\cdot c


3xy-4x = y+2

Add 4x to both sides we get;


3xy= y+2+4x


3xy-y=2+4x


y(3x-1)=2+4x


y = (4x+2)/(3x-1)

Step 4: Replace y with
f^(-1)(x)


f^(-1)(x) = (4x+2)/(3x-1)

Therefore, the inverse operation of a given function is:


f^(-1)(x) = (4x+2)/(3x-1)

User Colibrow
by
5.3k points